CD103+ tumor-resident CD8+ T cell numbers underlie improved patient survival in oropharyngeal squamous cell carcinoma. Issue 1 (10th June 2020) - Hewavisenti, Rehana; Ferguson, Angela; Wang, Kevin; Jones, Deanna; Gebhardt, Thomas; Edwards, Jarem; Zhang, Mei; Britton, Warwick; Yang, Jean; Hong, Angela; Palendira, Umaimainthan
Abstract : Background: Human Papillomavirus (HPV) associated oropharyngeal squamous cell carcinoma (OPSCC) is one of the fastest growing cancers in the Western world. When compared to OPSCCs induced by smoking or alcohol, patients with HPV+ OPSCC, have better survival and the mechanisms remain unclear. Methods: The Cancer Genome Atlas (TCGA) database was examined for genes associated with tissue-resident CD8+ T cells. Multiplex immunohistochemistry (IHC) staining was performed on tumor specimen taken from 35 HPV+ and 27 HPV- OPSCC patients. Results: TCGA database revealed that the expression of genes encoding CD103 and CD69 were significantly higher in HPV+ head and neck SCCs (HNSCC) than in HPV- HNSCC. Higher expression levels of these two genes were also associated with better overall survival. IHC staining showed that the proportion of CD103+ tumor-resident CD8+ T cells were significantly higher in HPV+ OPSCCs when compared to HPV- OPSCC. This higher level was also associated with both lower risk of loco-regional failure, and better overall survival. Importantly, patients with HPV- OPSCC who had comparable levels of CD103+ tumor-resident CD8+ T cells to those with HPV+ OPSCC demonstrated similar survival as those with HPV+OPSCC. Conclusion: Our results show that CD103+ tumor-resident CD8+ T cells are critical for protective immunity in both types of OPSCCs. Our data further suggest that the enhanced local protective immunity provided by tumor-resident T cell responses is the underlying factor driving favorable clinical outcomes in HPV+ OPSCCs over HPV- OPSCCs.